Density of zeros of eigenfunctions of sturm liouville problems - Pinasco, Juan Pablo (2013)
In this paper we study the asymptoticdensity of zeros of eigenfunctions of a weighted second order differential equation.Then, we consider the following nodal inverse problem: to determine the positivity andnegative zones of the weight function in the equation from the zeros of theeigenfunctions. We show that we can recover those zones under very mild assumptions.